Refractory Fulminant Acute Disseminated Encephalomyelitis (ADEM) in an Adult - Rodríguez-Porcel, Federico; Hornik, Alejandro; Rosenblum, Jordan; Borys, Ewa; Biller, José (Frontiers in Neurology, 2014)
Acute demyelinating encephalomyelitis (ADEM) is characterized by its rapid progression with variable symptoms and severity in adults and children. Multiple therapeutic options have been proposed, but solid evidence is yet to be gathered. We describe an adult man with a fulminant form of ADEM unresponsive to numerous treatment modalities